Austerity policies in the Eurozone: How they affect youth unemployment? - Carmen Diáz-Roldań; JoseĹuis Parada-Rodriǵuez; Nieves Carmona-Gonzaĺez (The Central European Review of Economics and Management (CEREM), 2019)
Aim: Analyse the effects of stabilization policies on youth unemployment, using government deficit besides the use of fiscal policy by the supply side; aimed to characterize the economic framework conditions under which fiscal policy could reduce youth unemployment.~Design/Research methods: We consider an economic framework featuring the use of monetary and fiscal rules within a monetary union. In this scenario, that should be representative of the Eurozone, we will analyse the effects of stabilization policies when dealing with a financial crisis which produces contractive effects on output and on employment. We will pay special attention to the conservativeness of the central bank, the degree of austerity of the fiscal authorities and the initial level of government debt. Those characteristics prove to be crucial for the sustainability of economic policies packages based on fiscal consolidation and the use of fiscal policy instruments by the supply side, when trying to deal with unemployment. And given that in the financial crisis effects have been hit Eurozone countries in a different manner, we will also differentiate monetary union's member countries according with their government debt and their unemployment path.~Conclusions/findings: Fiscal authorities should be no austere for fighting youth unemployment, when using fiscal policy by the supply side. In other words, when optimizing their loss function, they should give more weight to the output stabilization goal that to the government deficit reduction.~Originality/value of the article: Allowing for the use of both monetary and fiscal policy rules, in the scenario of a monetary union, our results could help us to stablish the conditions under which fiscal policy could help to alleviate youth unemployment.
Keywords: E62; E63; H6; 330; Monetary unions; fiscal consolidation; sustainable policies; youth unemployment